The effect of Anxiety on Narrative Writing Skills - Oktrifianty, Erdhita; MS, Zulela; Boeriswati, Endry (International Journal for Educational and Vocational Studies, 2020)
The object of this research is the influence of anxiety on the ability to write narration. Writing skill is an essential part of the language that must be internalized in elementary school students. In fact, there are still many students who find it is difficult to express their narrative ideas into a written language called writing. The difficulty is thought to raise anxiety in expressing language into written form. Students are afraid to start to write so that students, performance in writing affects the production of the resulting writing. Anxiety will produce a negative effect that adversely affects the student and hinders the writing activities undertaken. Therefore, the researcher raised this problem with respondents who were taken at grade V (five) level in the Public Elementary School in the Binaan III Region, Kebon Jeruk District, West Jakarta. The research method uses a quantitative approach with survey methods and path analysis techniques. Respondents used were 109 students from 3 elementary schools, namely SDN Kebon Jeruk 01, SDN Kebon Jeruk 08, and SDN Kebon Jeruk 10, by using the multistage cluster sampling technique. The research instrument was writing the narrative text for the variable narrative writing skill and a questionnaire for anxiety variables. The purpose of this study was to determine how much influence anxiety with the ability to write narration. The results of the study stated there was an influence between anxiety on the ability to write narratives of 202.